Evaluating retinal thickness classification in children: A comparison between pediatric and adult optical coherence tomography databases. - Tian Siew Pua; Mohd Izzuddin Hairol (PLoS ONE)
Purpose This study investigates the agreement of children's retinal thickness classification by color category between Topcon 3D OCT-1's built-in adult reference data and our new pediatric database and assesses the correlation of retinal thickness with age and spherical equivalent (SE). Methods 160 eyes of 160 healthy children (74 boys, 86 girls) aged 6-18 years (mean: 11.60 ± 3.28 years) were evaluated in this cross-sectional study. The peripapillary retinal nerve fibre layer (pRNFL) and macular thickness were determined for the 1st, 5th, 95th, and 99th percentile points. Cohen's κ value and specific agreement between pediatric data and adult reference database were estimated. The correlation between retinal thickness with age and SE was also determined. Results The mean thickness for the total RNFL, average macular, and central macula were 112.05±8.65 μm, 280.24±12.46 μm, and 220.55±17.53 μm, respectively. The overall agreement between the classification of the adult database and pediatric data for pRNFL was ≥90%, with discrepancies in 46 out of 150 eyes (30.67%); for macula, it was above 72%, with discrepancies in 93 out of 153 eyes (60.78%); and for ganglion cell complex and ganglion cell + inner plexiform layer (GCIPL) the agreement was above 84% and 85%, respectively. A significant level of agreement between pediatric data and adult reference data was achieved for temporal RNFL (κ = 0.65), macular perifoveal superior (κ = 0.67), and inferior (κ = 0.63) and inferior GCIPL (κ = 0.67). The correlations between age and retinal thickness were not significant (all p>0.05). Most retinal thickness parameters were positively associated with SE (Pearson's coefficient, r = 0.26 to 0.49, all p<0.05). Conclusions The overall agreement for pRNFL and macular thickness measurements in children with the adult reference database was between 72% and 90%. Children's retinal thickness was not significantly correlated with age but was positively associated with spherical equivalent.